battery

CN122889820APending Publication Date: 2026-10-09ZHUHAI COSMX BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611273324.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0003]现有技术中,胶纸通常以连续且均一的高覆盖率胶层涂布,并对电极组件的表面进行大面积覆盖,虽然提供了基本的粘结作用,但在电解液注入时,胶纸会严重阻碍电解液向电极组件内部渗透,导致电解液浸润路径受限,注液时间长、效率低且容易出现浸润不均的现象,影响电池的一致性和循环性能

Benefits of technology

(1)本发明有利于提升电解液对电极组件的浸润均匀性,维持胶纸对电极组件的束缚稳定性,避免注液过程中出现溢液或浸润不良以及电池循环或跌落后出现极片延展,增加电池出现短路失效的风险;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889820A_ABST
    Figure CN122889820A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of battery, and particularly relates to a battery. The battery comprises a shell and an electrode assembly, the electrode assembly has a first surface and a second surface oppositely arranged along a first direction and a connecting side surface; the electrode assembly comprises a gum paper comprising a first area and a second area, the first area partially covers the first surface and the second surface, and the second area partially covers the side surface; the gum paper comprises a base material layer and a gum layer; the sum of the areas of the gum layer of the gum paper on the electrode assembly is S, 0.01dm 2 ≤S≤0.5dm 2 ; the coverage rate of the gum layer in the unit area of the first area is greater than the coverage rate of the gum layer in the unit area of the second area; the residual liquid coefficient K of the battery satisfies: 1.1≤K≤2, and 2.5≤K / S≤60. Through the optimization of the structural design of the gum paper, the present application can improve the electrolyte infiltration uniformity while maintaining the adhesive strength of the gum paper to the electrode assembly, and effectively improve the interface stability of the gum paper and the cycle stability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and more specifically to a battery. Background Technology

[0002] With the rapid development of new energy vehicles and the energy storage industry, higher requirements have been placed on the energy density, cycle life, and safety of batteries. To ensure reliable fixation of the electrode components, prevent interference between the separator and the casing, and prevent electrode component delamination, adhesive tape is usually attached to the surface of the electrode components to bind and fix them, thereby ensuring the battery's packaging reliability and structural stability.

[0003] In the prior art, adhesive tape is usually coated with a continuous and uniform high coverage adhesive layer and covers a large area of ​​the electrode assembly surface. Although it provides basic bonding, the adhesive tape will seriously hinder the penetration of electrolyte into the electrode assembly during electrolyte injection. This results in a limited electrolyte wetting path, long injection time, low efficiency, and uneven wetting, which affects the consistency and cycle performance of the battery.

[0004] Therefore, how to improve the uniformity of electrolyte wetting while maintaining the reliability of the adhesive tape binding the electrode assembly, and further suppress cycle expansion and improve the stability of the interface structure, has become a technical problem that urgently needs to be solved in the current lithium-ion battery field. Summary of the Invention

[0005] The purpose of this invention is to overcome the aforementioned problems in the prior art and provide a battery. By optimizing the structural design of the adhesive tape, this invention can improve the electrolyte wetting uniformity while maintaining the adhesive strength of the tape to the electrode components, effectively enhancing the interfacial stability of the tape and the cycle stability of the battery.

[0006] The inventors have conducted extensive and targeted research, which effectively overcomes the aforementioned problems existing in the prior art, as detailed below: This invention proposes a partitioned adhesive tape, comprising a first region covering at least a portion of a first surface and at least a portion of a second surface of an electrode assembly, and a second region covering at least a portion of the side surface of the electrode assembly. By limiting the coverage difference of the adhesive layer in different regions, the coverage rate θ1 of the adhesive layer in the first region is greater than the coverage rate θ2 of the adhesive layer in the second region. This improves the uniformity of electrolyte wetting of the electrode assembly while ensuring the reliability and bonding stability of the adhesive tape for binding the electrode assembly. The reason is that the higher coverage rate of the first region enhances the adhesion strength with the electrode assembly, forming an effective constraint during cyclic expansion of the electrode sheet, preventing electrode sheet delamination and extension, thereby effectively reducing the risk of internal short circuits and tab breakage in the battery. The second region provides an effective wetting channel for the electrolyte to rapidly penetrate from the side surface into the interior of the electrode assembly, greatly shortening the wetting path, reducing the injection time, and effectively suppressing problems such as uneven wetting and low efficiency in high-energy-density batteries after injection. This structural design can effectively achieve synergistic optimization of "adhesive tape bonding" and "electrolyte wetting", and can significantly improve the wetting efficiency of electrolyte without sacrificing the adhesive tape bonding strength, thereby improving the cycle stability of the battery.

[0007] Since proper swelling of the adhesive layer in the electrolyte is crucial for enhancing its interfacial adhesion, this invention further correlates the residual electrolyte coefficient K of the battery with the sum of the areas S of the adhesive layers on the electrode assembly. By limiting K / S within a specific range, proper swelling of the adhesive layer by the electrolyte can be ensured, enhancing the interfacial adhesion between the adhesive layer and the electrode assembly. This prevents the adhesive layer from becoming excessively or insufficiently swollen, thus avoiding loss of its binding effect on the electrode assembly, thereby further improving the interfacial stability of the adhesive layer and the long-cycle stability of the battery.

[0008] Based on this, the inventors of this invention propose the following solution: This invention provides a battery, including a casing and an electrode assembly, the electrode assembly being located within the casing. The electrode assembly includes a positive electrode, a separator, and a negative electrode. Along a first direction of the electrode assembly, the separator is spaced between the positive and negative electrode. The electrode assembly has a first surface and a second surface disposed opposite each other along the first direction, and a side surface connecting the first surface and the second surface. The electrode assembly also includes adhesive tape extending from the first surface, through the side surface, to the second surface, and the adhesive tape adhering to at least a portion of the first surface and at least a portion of the second surface. The adhesive tape includes a first region and a second region, the first region being located on both sides of the second region, the first region covering at least a portion of the first surface and at least a portion of the second surface, and the second region covering at least a portion of the side surface. The adhesive tape includes a substrate layer and an adhesive layer located on at least one side surface of the substrate layer. The sum of the areas of the adhesive layers on the adhesive tape of the electrode assembly is S, 0.01 dm².2 ≤S≤0.5dm 2 The coverage of the adhesive layer in the first region per unit area is θ1, and the coverage of the adhesive layer in the second region per unit area is θ2, where θ1 > θ2; the residual electrolyte coefficient K of the battery satisfies: 1.1 ≤ K ≤ 2; K and S satisfy: 2.5 ≤ K / S ≤ 60.

[0009] By employing the above technical solution, the present invention has at least the following advantages compared with the prior art: (1) The present invention is beneficial to improve the uniformity of electrolyte wetting of electrode components, maintain the binding stability of adhesive tape on electrode components, avoid leakage or poor wetting during the injection process and electrode stretching after battery cycling or dropping, and increase the risk of battery short circuit failure. (2) The present invention can improve the stability of the connection interface between the adhesive tape and the electrode assembly, reduce the risk of electrode assembly delamination caused by the decrease of the binding effect of the adhesive tape on the electrode assembly during battery use and the resulting increase in the degree of lithium plating on the negative electrode, and improve the long-cycle stability of the battery.

[0010] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. Attached Figure Description

[0011] Figure 1 The diagram shown is a schematic diagram of the electrode assembly in an embodiment of the present invention.

[0012] Figure 2 The figure shown is a schematic diagram of the planar structure of the adhesive tape in an embodiment of the present invention.

[0013] Figure 3 The figure shown is a three-dimensional structural diagram of the adhesive tape in an example of the present invention.

[0014] Figure label: 10. Adhesive tape; 10a. First adhesive tape; 10b. Second adhesive tape; 10c. Third adhesive tape; 11. Substrate layer; 12. Adhesive layer; 20. First zone; 30. Second zone. Detailed Implementation

[0015] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.

[0016] This invention provides a battery including a casing and an electrode assembly. The electrode assembly is located within the casing and includes a positive electrode, a separator, and a negative electrode. Along a first direction of the electrode assembly, the separator is spaced between the positive and negative electrode. The electrode assembly has a first surface and a second surface disposed opposite each other along the first direction, and a side surface connecting the first surface and the second surface. It should be noted that the first direction refers to the thickness direction of the electrode assembly, i.e., the stacking direction in which the positive electrode, separator, and negative electrode are sequentially stacked.

[0017] In this invention, the electrode assembly further includes adhesive tape extending from the first surface, through the side surface, to the second surface. The adhesive tape adheres to at least a portion of the first surface and at least a portion of the second surface. The adhesive tape includes a first region and a second region, with the first region located on both sides of the second region. The first region covers at least a portion of the first surface and at least a portion of the second surface, and the second region covers at least a portion of the side surface. It should be noted that the number of adhesive tapes in this invention is not less than two pieces. By using multiple pieces of adhesive tape, it is possible to more flexibly adapt to the shape and size of different electrode assemblies, making the binding force applied by the adhesive tape to the electrode assembly more uniformly distributed, meeting the requirement for uniform electrolyte wetting in different parts of the electrode assembly, and further improving the structural stability and electrolyte wetting consistency of the electrode assembly. The adhesive tape includes a substrate layer and an adhesive layer located on at least one side surface of the substrate layer; the sum of the areas of the adhesive layers of the adhesive tape on the electrode assembly is S, 0.01 dm². 2 ≤S≤0.5dm 2 (e.g., 0.01dm) 2 0.015dm 2 0.02dm 2 0.03dm 2 0.04dm 2 0.05dm 2 0.06dm 2 0.08dm 2 0.1dm 2 0.12dm 2 0.15dm 2 0.18dm 2 0.2dm 2 0.25dm 2 0.3dm 2 0.35dm 2 0.4dm 2 0.45dm 2 0.5dm 2(or within the range of any two of the above values). It should be noted that: "the sum S of the areas of the adhesive layers of the adhesive tape on the electrode assembly" as described in this invention refers to the cumulative area of ​​all adhesive layers contained in all the adhesive tapes attached to the surface of the electrode assembly. dm 2 The term S refers to square decimeters. When S is within the above range, it ensures the adhesion between the adhesive tape and the electrode assembly, guarantees the overall structural stability of the battery, prevents electrode assembly delamination, and improves the battery's drop safety. If S is less than 0.01 dm... 2 If the total bonding area between the adhesive tape and the electrode assembly is too small, the adhesive tape's binding force on the electrode assembly is insufficient. When the battery is subjected to mechanical impact, drop, or undergoes multiple charge-discharge cycles resulting in significant volume expansion stress, the electrode assembly is prone to interlayer separation. If S is greater than 0.5 dm 2 If the adhesive layer occupies a large proportion on the surface of the electrode assembly, it will significantly hinder the penetration of the electrolyte, resulting in a longer injection time and areas of insufficient wetting inside the electrode assembly.

[0018] In this invention, S can be obtained through conventional methods in the art. For example, after discharging the battery to 0% SOC, the electrode assembly is disassembled and removed. All adhesive tape is carefully and completely peeled off from the surface of the electrode assembly. Subsequently, the surface morphology of the peeled adhesive tape is observed using a scanning electron microscope (SEM). Based on the differences in grayscale, texture, or elemental contrast between the adhesive layer and the substrate layer, the adhesive layer region and the substrate region are identified and divided using image binarization processing. On this basis, a 3D profilometer is used to perform three-dimensional morphological scanning and data acquisition on the divided adhesive layer region. The three-dimensional contours of all adhesive layers are fitted using the accompanying analysis software, and the actual geometric area of ​​each adhesive layer is automatically calculated. The total area of ​​all adhesive layers on all adhesive tapes on the electrode assembly is summed, and the resulting sum is S.

[0019] This invention does not impose a particular limitation on the shape of the adhesive layer. The adhesive layer can be a continuous, integral structure on the surface of the substrate layer, such as forming a single rectangular adhesive layer area; or it can be a discrete, discontinuous structure, consisting of multiple adhesive layer units spaced apart from each other. In the case of a discontinuous adhesive layer structure, the planar projection shape of a single adhesive layer unit can be, for example, circular, elliptical, prismatic, trapezoidal, or other regular or irregular geometric shapes. When the adhesive layer is distributed discretely, the sum of the areas S of the adhesive layers on the adhesive paper of the electrode assembly is the sum of the projected areas S of all adhesive layer units on the substrate layer surface. By employing adhesive layers of a specific shape or distribution structure in the first and / or second regions, channels conducive to electrolyte penetration can be constructed while ensuring adhesion, further optimizing the wetting path and efficiency of the electrolyte at the interface between the adhesive paper and the electrode assembly.

[0020] In this invention, the coverage rate of the adhesive layer in the first area per unit area is θ1, and the coverage rate of the adhesive layer in the second area per unit area is θ2, where θ1 > θ2. θ2 and θ2 can be understood as follows: in the first or second area of ​​the adhesive paper, a square area of ​​25μm × 25μm is used as a unit area statistical unit (i.e., the statistical area is 25μm × 25μm = 625μm). 2 The coverage area of ​​the adhesive layer on the surface of the substrate layer within the statistical unit is measured (i.e., the projected area of ​​the adhesive layer on the surface of the substrate layer). The sum of the coverage areas is divided by the statistical area, and then multiplied by 100%. The resulting percentage is the coverage rate θ1 of the adhesive layer in the first area per unit area or the coverage rate θ2 of the adhesive layer in the second area per unit area.

[0021] In one instance, 50% / 625μm 2 ≤θ1≤100% / 625μm 2 (e.g., 50% / 625μm) 2 55% / 625μm 2 60% / 625μm 2 65% / 625μm 2 70% / 625μm 2 75% / 625μm 2 80% / 625μm 2 85% / 625μm 2 90% / 625μm 2 95% / 625μm 2 100% / 625μm 2 Or within the range of any two of the above values).

[0022] In one instance, 0% / 625μm 2 ≤θ2≤49% / 625μm 2 (For example, 0% / 625μm) 2 5% / 625μm 2 10% / 625μm 2 15% / 625μm 2 20% / 625μm 2 25% / 625μm 2 30% / 625μm 2 35% / 625μm 2 40% / 625μm 2 45% / 625μm 2 49% / 625μm 2 Or within the range of any two of the above values).

[0023] This invention, by setting the first region as a high-adhesion zone and the second region as a low-adhesion zone or an adhesive-free zone, can create functionally differentiated areas on the same adhesive paper. The first region focuses on ensuring the structural strength and binding force of the electrode assembly, while the second region focuses on ensuring rapid and uniform electrolyte penetration. When the electrolyte is injected, it preferentially and rapidly penetrates into the interior of the electrode assembly from the second region. Simultaneously, the first region, with its high adhesive layer coverage, ensures binding force in the thickness direction of the electrode assembly, maintaining tight interlayer contact between the electrode and the separator during cycling. This prevents internal short circuits caused by electrode stretching and the risk of electrode root breakage due to stretching of the electrode tabs. When θ1 reaches 100% / 625μm... 2 When the adhesive layer is fully distributed in the first zone, it can provide the maximum adhesive strength in that area; when θ2 is 0% / 625μm 2 In this case, the second zone only has a substrate layer and no adhesive layer, thus minimizing the penetration resistance of the electrolyte.

[0024] In this invention, θ1 and θ2 can be obtained using conventional methods in the art. For example, 15 regions are randomly selected from each of the first and second regions of a single adhesive strip, each region having an area of ​​25μm × 25μm. The contour of the adhesive layer in each region of the first and second regions is captured and simulated using SEM at a magnification of 5000x, and the area of ​​the adhesive layer in each region is measured. The area ratio of the adhesive layer in each region is calculated, and the average value is taken. At least 3 adhesive strips are selected for testing, and the final average value is taken to obtain θ1 and θ2.

[0025] In this invention, the residual electrolyte coefficient K of the battery satisfies: 1.1g / Ah ≤ K ≤ 2g / Ah (for example, within the range of 1.1g / Ah, 1.2g / Ah, 1.3g / Ah, 1.4g / Ah, 1.5g / Ah, 1.6g / Ah, 1.7g / Ah, 1.8g / Ah, 1.9g / Ah, 2g / Ah, or any two of the above values). The residual electrolyte coefficient K is a parameter used to characterize the amount of electrolyte retained inside the battery, and it is defined as the mass of electrolyte corresponding to a unit battery capacity. Specifically, the formula for calculating K is: K = [electrolyte mass (g) / battery capacity (Ah)]. Wherein, battery capacity refers to the rated capacity that the battery can release between preset charge and discharge cutoff voltages; the specific test method for the K value is as follows: weigh the finished battery and record it as m0; then disassemble the battery in an inert atmosphere or dry environment, centrifuge to separate the electrolyte, immerse the disassembled shell, separator, positive electrode, negative electrode and tabs in acetonitrile solvent, then take out the above components and bake them at 80°C for 2 hours, weigh them and record them as m1; then the electrolyte mass is m0-m1, and then calculate the K value according to the battery capacity. It should be noted that the residual liquid coefficient K of the battery can be controlled by a variety of conventional process methods in the art, such as including but not limited to: adjusting the porosity of the separator and electrode to change the amount of residual liquid inside the battery; controlling the injection volume to limit the total amount of electrolyte from the source; for batteries using soft-pack packaging, changing the amount of residual liquid inside the battery by adjusting the evacuation time and pressure in the second sealing process.

[0026] When K is too small (e.g., less than 1.1 g / Ah), the electrolyte content inside the battery is too low. On the one hand, this will lead to insufficient electrolyte wetting of the electrode components, obstruction of lithium-ion transport paths, increased battery polarization, increased internal resistance, and a surge in Joule heat inside the battery, resulting in decreased long-cycle performance. Furthermore, the local temperature of the battery may rise excessively during charging / discharging, accelerating aging and posing a risk of thermal runaway. On the other hand, the adhesive layer of the adhesive tape will swell moderately after absorbing the electrolyte, causing the polymer chains in the adhesive layer to stretch, reducing the surface energy of the adhesive layer, and thus increasing the contact area between the adhesive layer and the electrode component surface, improving interfacial adhesion. If the K value is too low, there is insufficient electrolyte to induce moderate swelling of the adhesive layer, the polymer chains in the adhesive layer cannot stretch fully, the adhesion strength between the adhesive tape and the electrode component is not enhanced, and the binding effect of the adhesive tape on the expansion of the electrode sheet is weakened. When K is too large (e.g., greater than 2g / Ah), the electrolyte content inside the battery is too high, which can easily cause electrolyte to overflow and contaminate the casing during the electrolyte injection process, affecting the process yield. At the same time, too much electrolyte will cause the polymer in the adhesive layer to swell excessively, the cohesive strength of the adhesive layer itself will decrease significantly, and the adhesive layer will be prone to breakage, resulting in the failure of the binding effect of the adhesive paper.

[0027] In this invention, the sum of the residual electrolyte coefficient K of the battery and the area S of the adhesive layer of the adhesive tape on the electrode assembly satisfies: 2.5 ≤ K / S ≤ 60 (for example, within the range of any two values ​​of 2.5, 3, 4, 5, 6, 7, 8, 9, 10, 12, 15, 18, 20, 25, 30, 35, 40, 45, 50, 55, 60, or above). This can be understood as 2.5 ≤ K / S ≤ 60, where K is in g / Ah and S is in dm³. 2 When K is 1.5 g / Ah and S is 0.2 dm³, use the corresponding numerical values ​​for calculation. 2 When K=1.5 and S=0.2, K / S is 7.5. When K / S is too small (e.g., less than 2.5), it means there is too little electrolyte available inside the battery, and the total area S of the adhesive layer is relatively large. In this case, the swelling degree of the adhesive layer is insufficient, the adhesion between the adhesive layer and the electrode assembly surface is weakened, and excessive adhesive layer also hinders electrolyte penetration. When K / S is too large (e.g., greater than 60), it means there is too much electrolyte available inside the battery, and the total area S of the adhesive layer is relatively small. In this case, the bonding area is insufficient to firmly bind the electrode assembly, and the adhesive layer is prone to excessive swelling under the action of excessive electrolyte, reducing cohesive strength, making the adhesive layer prone to failure, and affecting the interfacial stability of the adhesive paper. Therefore, this invention controls K / S within a suitable range to ensure that the electrolyte content inside the battery can fully wet the electrode assembly and moderately swell the adhesive layer, avoiding problems such as insufficient adhesive bonding area, thereby effectively improving the electrolyte wetting speed and uniformity, as well as the adhesive strength of the adhesive paper.

[0028] In one instance, 0.03dm 2 ≤S≤0.4dm 2 .

[0029] In one instance, 4 ≤ K / S ≤ 40.

[0030] In some embodiments of the present invention, the electrode assembly is a stacked core structure. The stacked core structure includes the positive electrode sheet, the separator, and the negative electrode sheet stacked sequentially. The electrode assembly includes a first tab; the electrode assembly has a third surface and a fourth surface disposed opposite to each other along a second direction; the electrode assembly has a first end face and a second end face disposed opposite to each other along a third direction, the first end face being closer to the extension direction of the first tab, and the second end face being farther away from the extension direction of the first tab; the side surface includes the third surface, the fourth surface, the first end face, and the second end face. It is understood that this example exemplifies the configuration of the side surface when the electrode assembly is in a cuboid or square configuration. When the electrode assembly adopts other three-dimensional configurations, such as, but not limited to, L-shaped, concave, and other irregular structures, the number and shape of the surfaces included in its side surface will change accordingly, and may include, but are not limited to, the four surfaces described above: the third surface, the fourth surface, the first end face, and the second end face. In other words, the side surface of the present invention generally refers to all surfaces connecting between the first surface and the second surface and surrounding the periphery of the electrode assembly. It should be noted that the second direction refers to the width direction of the electrode assembly, and the third direction refers to the height direction of the electrode assembly. The first direction is perpendicular to the second direction and the third direction. The adhesive tape includes a first adhesive tape, a second adhesive tape, and a third adhesive tape. Each of the first, second, and third adhesive tapes independently includes a first region and a second region, with the first region located on both sides of the second region. The first region of the first adhesive tape covers a portion of the first surface and a portion of the second surface; the second region of the first adhesive tape covers a portion of the third surface; the first region of the second adhesive tape covers a portion of the first surface and a portion of the second surface; the second region of the second adhesive tape covers a portion of the fourth surface; the first region of the third adhesive tape covers a portion of the first surface and a portion of the second surface; and the second region of the third adhesive tape covers a portion of the second end face. It should be understood that this explanation uses three adhesive tapes as an example and does not constitute a limitation on the number of adhesive tapes. The number of adhesive tapes and their positions on the side surfaces can be flexibly adjusted according to the binding force requirements of the electrode assembly and the specific structure of the side surfaces. For example, two or more pieces of adhesive tape can be used to cover multiple side surfaces, as long as each piece of adhesive tape has a first area that is bonded to at least a portion of the first surface and at least a portion of the second surface, and a second area that is bonded to the corresponding side surface.

[0031] In one example, the separator covers the negative electrode sheet, and at least one edge of the separator extends beyond the corresponding edge of the negative electrode sheet. The portions extending beyond the negative electrode sheet in at least two adjacent separator layers are bonded together to form a separator edge heat-sealing area. The separator edge heat-sealing area is attached to the side surface of the stacked core structure. The second area of ​​the first adhesive tape, the second area of ​​the second adhesive tape, and the second area of ​​the third adhesive tape each independently cover at least a portion of the separator edge heat-sealing area.

[0032] To prevent direct contact or micro-short circuits between the positive and negative electrodes that may occur due to electrode misalignment, edge burrs, or electrode extension during cycling in the stacked core structure, the separator in this invention covers the negative electrode. On at least one side surface of the electrode assembly, the edges of at least two adjacent separator layers extend beyond the corresponding edge of the negative electrode. The portion of the separator extending beyond the edge of the negative electrode is bonded together by hot pressing or hot stamping to form a separator hot-stamped edge area. This hot-stamped edge area constrains the electrode edge, preventing electrode slippage when the electrode assembly is subjected to mechanical impact or the negative electrode expands in volume, thereby maintaining the relative positional stability between the electrode and the separator and improving the overall structural stability of the electrode assembly. However, this hot-stamped edge area also increases the rigidity of the separator edge to some extent, which can easily cause wear to the battery casing during battery cycling. Furthermore, the tight adhesion of the separator edge after hot stamping also increases the wetting resistance of the electrolyte. Based on this, this invention makes the second area of ​​the adhesive paper cover at least a portion of the side surface, that is, the second area of ​​the adhesive paper overlaps with at least a portion of the separator hot-stamped edge area. This design not only reduces friction between the edge of the diaphragm heating zone and the outer shell, but also ensures that the electrolyte penetrates into the electrode assembly, thereby guaranteeing the synergistic optimization of the electrode assembly's structural stability and the uniform wetting of the electrolyte.

[0033] In other embodiments of the present invention, the electrode assembly is a wound core structure. The positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound to form a wound core. The electrode assembly includes a second tab, and the electrode assembly has a third end face and a fourth end face disposed opposite to each other along the height direction, the third end face being close to the extending direction of the second tab, and the fourth end face being away from the extending direction of the second tab. The side surface includes the third end face and the fourth end face. The adhesive tape includes a fourth adhesive tape and a fifth adhesive tape, each of the fourth adhesive tape and the fifth adhesive tape independently including a first region and a second region, the first region being located on both sides of the second region. The first region of the fourth adhesive tape covers a portion of the first surface and a portion of the second surface, and the second region of the fourth adhesive tape covers a portion of the third end face; the first region of the fifth adhesive tape covers a portion of the first surface and a portion of the second surface, and the second region of the fifth adhesive tape covers a portion of the fourth end face.

[0034] like Figure 1 The diagram shows a schematic representation of the electrode assembly in an embodiment of the present invention. As can be seen from the diagram, the adhesive tape 10 includes a first adhesive tape 10a, a second adhesive tape 10b, and a third adhesive tape 10c. The adhesive tape 10 includes a first region 20 and a second region 30. For example... Figure 2 The diagram shows a planar structure of the adhesive tape in an embodiment of the present invention. As can be seen from the diagram, the adhesive tape 10 includes a first region 20 and a second region 30, with the first region located on either side of the second region. Figure 3 The figure shows a three-dimensional structural diagram of the adhesive tape in an embodiment of the present invention. As can be seen from the figure, the adhesive tape 10 includes a substrate layer 11 and an adhesive layer 12 located on at least one side of the substrate layer; wherein the coverage rate θ2 of the adhesive layer in the second area per unit area is 0%, and the second area has only the substrate layer and no adhesive layer.

[0035] In this invention, the negative electrode sheet includes a negative current collector and a negative active layer located on at least one side of the surface of the negative current collector. The negative active layer includes a silicon-based material, and the mass content of silicon element in the negative active layer is 4%-60% (for example, within the range of any two values ​​of 4%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or more).

[0036] In one example, the silicon content in the negative electrode active layer is 5%-50% by mass.

[0037] Silicon-based materials exhibit significant volume expansion during charging and discharging (up to 300% or more), leading to problems such as electrode folding, excessive stretching, and delamination between adjacent electrodes and the separator. This can easily cause internal short circuits or external tab breakage. The adhesive tape of this invention ensures effective adhesion to the electrode assembly, effectively restraining the silicon-based material during its dramatic volume expansion, reducing the risks of electrode delamination, folding, and excessive stretching, and further improving the structural stability of the electrode assembly. When the silicon content in the negative electrode active layer exceeds 60%, the volume expansion of the negative electrode during cycling becomes too drastic, increasing the risk of electrode stretching. Furthermore, excessive silicon content consumes a large amount of electrolyte during the initial battery formation process, resulting in insufficient electrolyte inside the battery and low residual electrolyte levels. In subsequent cycles, there is insufficient electrolyte to continuously repair the unstable SEI film (solid electrolyte membrane) formed during volume expansion. The repair process of the SEI film in the later stages of cycling becomes difficult to maintain, leading to the loss of its protective function. More silicon surface is exposed in the electrolyte, triggering more severe side reactions, accelerating electrolyte depletion and lithium ion loss. The electrolyte consumption increases significantly, making it difficult to maintain the residual electrolyte coefficient K within the target range and affecting the battery's cycle stability.

[0038] In this invention, the mass content of silicon in the negative electrode active layer can be obtained by conventional methods in the art. For example, after discharging the battery to 0% SOC, the negative electrode sheet is disassembled and soaked in dimethyl carbonate (DMC) solvent for 12 hours, then rinsed with DMC solvent to remove lithium salts adhering to the negative electrode sheet. After drying, the negative electrode sheet is subjected to high-temperature treatment at 400°C in an inert atmosphere for 2 hours (e.g., in a tube furnace under nitrogen or argon atmosphere). The negative electrode active layer can then be peeled off from the negative electrode current collector, and the negative electrode active layer is collected as a test sample. Using a thermogravimetric analyzer (e.g., a TGA 550 thermogravimetric analyzer), the test sample amount is 5mg-15mg. Under an air or oxygen atmosphere, the temperature is increased from room temperature (25°C) to 900°C at a rate of 10°C / min, and held at 900°C for 40 minutes. This allows the non-silicon components in the negative electrode active layer to volatilize while the silicon is fully oxidized to silicon dioxide. Weigh the residual material. The silicon content in the negative electrode active layer can be obtained by the following formula: Silicon content in the negative electrode active layer = 7 × mass of residual material / (15 × mass of test sample).

[0039] In this invention, the battery further includes an electrolyte comprising a carboxylic acid ester, which includes a non-fluorinated linear carboxylic acid ester, specifically at least one selected from ethyl propionate (EP), propyl propionate (PP), and ethyl butyrate (EB). These carboxylic acid esters have relatively low viscosity, allowing them to easily penetrate between the polymer molecular chains of the adhesive layer in the adhesive paper, causing moderate swelling of the adhesive layer. This reduces the surface energy of the adhesive layer molecules, thereby increasing the actual contact area between the adhesive layer and the electrode assembly surface, further enhancing the interfacial adhesion between the adhesive paper and the electrode assembly.

[0040] In one example, the carboxylic acid ester in the electrolyte has a mass content (C1) of 5%-68% (e.g., within the range of any two of the following values: 5%, 8%, 10%, 13%, 15%, 18%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 68%). If C1 is below 5%, its swelling-promoting effect on the adhesive layer is not significant enough, resulting in insufficient improvement in adhesion; if C1 is above 68%, it may over-dilute the electrolyte, affecting the battery's ionic conductivity and cycle performance.

[0041] In one instance, C1 ranges from 8% to 40%.

[0042] In this invention, the electrolyte further includes fluoroethylene carbonate. During charging and discharging, silicon-based materials undergo dramatic volume expansion and contraction, making the surface solid electrolyte interphase (SEI) film prone to rupture. This continuously exposes fresh active surfaces, triggering the continuous decomposition of the electrolyte and consuming limited active lithium and electrolyte. Fluoroethylene carbonate can participate in the formation of a fluorinated, more flexible SEI film on the surface of the silicon-based anode. This film better adapts to the volume changes of the silicon-based material, is less prone to rupture, effectively suppressing side reactions, further stabilizing the electrode interface, and reducing additional electrolyte consumption.

[0043] In one example, the fluoroethylene carbonate (C2) in the electrolyte has a mass content of 5%-25% (e.g., within the range of any two of the following values: 5%, 6%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%). When C2 is below 5%, the resulting fluorinated SEI film is not sufficiently complete and dense, providing limited protection for the negative electrode; when C2 is above 25%, the fluorine content in the SEI film is too high, which may increase the film's impedance and affect the battery's rate performance and cycle performance.

[0044] In this invention, the electrolyte further includes non-fluorinated cyclic carbonates, including ethylene carbonate (EC) and / or propylene carbonate (PC). Non-fluorinated cyclic carbonates typically have high dielectric constants, which can promote the dissociation of lithium salts. Furthermore, during the co-formation process with fluoroethylene carbonate, they can adjust the composition and morphology of the SEI film, improving the film's density and lithium-ion conductivity.

[0045] In one example, the mass content C3 of the non-fluorinated cyclic carbonate in the electrolyte is 5%-50% (e.g., within the range of any two values ​​of 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 45%, 50% or more).

[0046] In this invention, C1, C2 and C3 can be obtained by methods conventional in the art, such as gas chromatography (GC), gas chromatography-mass spectrometry (GCMS) or liquid chromatography (LC).

[0047] In one instance, 0.3 ≤ (C2 + C3) / C1 ≤ 10 (for example, within the range of any two of the following values: 0.3, 0.5, 0.8, 1, 1.5, 2, 2.5, 3, 4, 5, 6, 7, 8, 9, 10).

[0048] In one instance, 0.3 ≤ (C2 + C3) / C1 ≤ 5.

[0049] When (C2+C3) / C1 is greater than 10, it means that the total amount of carbonate is relatively excessive, while the amount of carboxylic acid ester is relatively insufficient. This will lead to a higher overall viscosity of the electrolyte, making it difficult for the electrolyte to wet quickly and effectively maintain the proper swelling of the adhesive layer. Consequently, the bonding strength between the adhesive layer and the electrode assembly cannot be fully improved. When (C2+C3) / C1 is less than 0.3, it means that the content of carboxylic acid ester is relatively excessive, while the content of carbonate is relatively insufficient. At this time, although the electrolyte viscosity is low, the SEI film formed on the negative electrode surface is not stable enough. It is prone to repeated rupture and regeneration during cycling, triggering side reactions. Active lithium and electrolyte are continuously consumed. At the same time, the adhesive layer may swell excessively, leading to adhesion failure. This will prevent the adhesion between the adhesive tape and the electrode assembly from being improved, resulting in problems such as adhesive tape breakage, electrode assembly delamination, and drop failure. Therefore, by controlling (C2+C3) / C1 within the above range, the present invention can maintain a suitable viscosity of electrolyte to ensure sufficient wetting of electrode components and moderate swelling of the adhesive layer, while forming a sufficiently stable SEI film to protect the silicon-based anode and take into account the cycle stability of the battery.

[0050] In this invention, the substrate layer comprises at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinyl chloride, polytetrafluoroethylene, polyacrylonitrile, polyamide, polyimide, polyethylene terephthalate, polybutylene terephthalate, poly(p-phenylene terephthalamide), poly(m-phenylene isophthalamide), and their derivatives.

[0051] In one example, the substrate layer comprises at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinyl chloride, polytetrafluoroethylene, polyacrylonitrile, polyamide, polyimide, polyethylene terephthalate, polybutylene terephthalate, poly(p-phenylene terephthalate), and poly(m-phenylene isophthalate).

[0052] In this invention, the adhesive layer comprises a polymer, the polymer including at least one of the following groups: carboxyl, ester, hydroxyl, phenyl, cyano, epoxy, amino, phenolic hydroxyl, urethane, carbon-carbon double bond, carbonyl, methyl, methylene, and carbon-hydrogen bonds on an aromatic ring. The term "carbon-hydrogen bonds on an aromatic ring" refers to a polymer molecule containing an aromatic ring structure with unsubstituted carbon-hydrogen bonds on the aromatic ring.

[0053] In one example, the monomers forming the polymer include at least one of a first monomer, a second monomer, and a third monomer. The first monomer includes at least one of n-butyl acrylate, ethyl acrylate, n-octyl acrylate, isobutyl acrylate, nonyl acrylate, n-decyl acrylate, lauryl methacrylate, lauryl acrylate, isodecyl acrylate, isoprene, butadiene, ethylene, and ethylene and butene; the second monomer includes at least one of vinyl acetate, methyl acrylate, methyl methacrylate, styrene, acrylonitrile, ethyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate, and isobornyl acrylate; the third monomer includes at least one of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, 4-hydroxybutyl acrylate, ethylene glycol, acrylic acid, methacrylic acid, acrylamide, methacrylamide, N,N-dimethylacrylamide, and glycidyl methacrylate.

[0054] In one example, the monomers forming the polymer include a first monomer, a second monomer, and a third monomer. The mass content w1 of the first monomer in the polymer is 40%-70% (e.g., within the range of any two values ​​of 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68%, 70%, or above). The first monomer typically has a low glass transition temperature, providing flexibility and tackiness to the polymer. The second monomer has a relatively high glass transition temperature, providing cohesive strength and rigid support to the polymer. The third monomer may introduce crosslinkable functional groups or specific polar groups to control the crosslinking density, cohesive force, and interfacial interactions of the adhesive layer.

[0055] When w1 is below 40%, the content of the first monomer in the adhesive layer is too low, the adhesive layer is too hard, the initial adhesion is insufficient, and the adhesive paper is difficult to form an effective bond with the surface of the electrode assembly. When w1 is above 70%, the content of the first monomer in the adhesive layer is too high, the support is insufficient, and the adhesive layer is prone to creep under continuous pressure, which leads to the collapse of the liquid storage cavity or the slippage of the bonding interface.

[0056] In this invention, the thickness h1 of the substrate layer is 5μm-50μm (for example, within the range of any two values ​​of 5μm, 8μm, 10μm, 12μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm or 50μm or above).

[0057] In one instance, h1 is 5μm-40μm.

[0058] In this invention, the thickness h2 of the adhesive layer is 2μm-12μm (for example, within the range of 2μm, 3μm, 4μm, 5μm, 6μm, 8μm, 10μm, 12μm, or any two of the above values). When h2 is less than 2μm, the adhesion between the adhesive layer and the electrode assembly is insufficient, and the binding stability of the adhesive paper on the electrode assembly is poor. When h2 is greater than 12μm, the adhesive layer is too thick, the swelling after absorbing the electrolyte increases, the cohesive strength of the adhesive layer decreases, and the adhesive layer is prone to breakage, causing the binding effect of the adhesive paper to fail. In addition, an excessively thick adhesive layer will occupy too much of the limited space inside the battery.

[0059] In this invention, the thickness h1 of the substrate layer and the thickness h2 of the adhesive layer can be obtained by conventional methods in the art. For example, the battery is discharged to 0% SOC, the adhesive paper is disassembled and removed, and the positions of the substrate layer and adhesive layer are determined by SEM observation. Ten test sites are randomly selected on the surface of the substrate layer and adhesive layer respectively, the thickness of each site is measured, and the average value is taken.

[0060] In this invention, the air permeability of the first zone is G1, the air permeability of the second zone is G2, and G1 / G2 > 1.5 (for example, within the range of any two values ​​of 1.6, 1.8, 2, 2.5, 5, 10, 20, 50, 80, 100, 500 or above).

[0061] Air permeability refers to the time required for 100cc of gas to pass through a unit area of ​​sample under a specific pressure. A smaller value indicates better air permeability and less resistance to gas passage. The adhesive tape of this invention employs a zoned structure design, resulting in differences in air permeability between different zones. The air permeability of the first zone is greater than that of the second zone, meaning the second zone has better air permeability than the first. This difference allows the electrolyte to preferentially penetrate from the second zone, which adheres to the side surface, while the first zone maintains better sealing and adhesion.

[0062] In one instance, G2 is 50S / 100cc-500S / 100cc (e.g., 50S / 100cc, 80S / 100cc, 100S / 100cc, 120S / 100cc, 150S / 100cc, 200S / 100cc, 250S / 100cc, 300S / 100cc, 350S / 100cc, 400S / 100cc, 450S / 100cc, 500S / 100cc or any two of the above values).

[0063] In this invention, G1 and G2 can be obtained by methods conventional in the art, such as by testing with an air permeability meter.

[0064] In this invention, the substrate layer comprises a porous structure, and the pore size of the substrate layer is 10nm-100nm (for example, within the range of any two values ​​of 10nm, 15nm, 20nm, 25nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, or above). The pore size of the substrate layer can be measured by conventional methods in the art. For example, a sample of the substrate layer to be tested is taken, dried, and then observed and images are acquired on its surface or cross-section using SEM at an appropriate magnification. At least 20 pore sizes in the image are measured using image analysis software, and the average value is taken.

[0065] In this invention, the porosity of the substrate layer is 20%-80% (e.g., within the range of any two values ​​of 20%, 25%, 30%, 35%, 40%, 50%, 60%, 70%, 80%, or above). The porosity of the substrate layer can be obtained by conventional methods in the art, such as the gas displacement method. A sample of the substrate layer to be tested is taken, cut into a regular shape (e.g., square or circular), its length, width, and height are measured, its volume is calculated, and its mass is accurately weighed to calculate the apparent density, denoted as ρ1. Subsequently, the density of the substrate layer is measured under dry conditions using a gas displacement specific gravity bottle (e.g., a helium specific gravity bottle), denoted as ρ2. Finally, the porosity of the substrate layer is calculated according to the formula porosity (%) = (ρ2-ρ1) / ρ2×100%. This test should be conducted under constant temperature and humidity conditions to eliminate the influence of environmental factors on the measurement results.

[0066] In one example, the porosity of the substrate layer is 30%-50%.

[0067] By designing a porous structure, it is beneficial to promote the penetration of electrolyte into the adhesive tape. Appropriate pore size and porosity help to balance the adhesive tape's liquid absorption capacity, negative pressure adsorption and positioning ability, and structural stability. If the pore size is too large or the porosity is too high, it will weaken the stability of the adhesive tape substrate; if the pore size is too small or the porosity is too low, it will increase the resistance to electrolyte penetration into the electrode assembly.

[0068] In this invention, the negative electrode sheet further includes a carbon-based material, which includes at least one of graphite, hard carbon, and soft carbon.

[0069] In this invention, the silicon-based material includes at least one of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy.

[0070] In one example, the average particle size D1 of the carbon-based material is 10 μm-20 μm (e.g., within the range of any two of the following values: 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm).

[0071] In one example, the average particle size D2 of the silicon-based material is 2μm-15μm (e.g., within the range of any two of the following values: 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 12μm, 15μm).

[0072] In this invention, D1 and D2 can be obtained by conventional methods in the art, such as discharging the battery to 0% SOC, disassembling and removing the negative electrode, polishing its cross-section with an argon-ion polisher, and then imaging it in an SEM device to obtain a clear SEM image. At least 20 carbon-based and silicon-based material particles are selected from the SEM image, and the particle size of each particle is measured and averaged. If the particle is a regular circle in the mirror image, then the particle size is the diameter of that circle. If the particle is not a "regular circle" in the mirror image, then the particle size is the diameter of an equivalent circle with the same area as the "regular circle".

[0073] In one example, the sphericity of the silicon-based material is 0.6-1 (e.g., within the range of any two values ​​from 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1). The sphericity of the silicon-based material can be tested using conventional methods in the art. For example, the battery is discharged to 0% SOC, the negative electrode is disassembled and removed, or the negative electrode is directly removed. After polishing the cross-section of the negative electrode with an argon ion mill, it is observed in a SEM device using backscatter imaging mode. Using image processing software (e.g., Image Pro Plus), at least 10 silicon-based material particles with continuous and smooth contours are selected from the SEM image of the silicon-based material at a certain magnification (e.g., 2500x). The perimeter and area of ​​each particle are measured, and the perimeter equivalent radius r1 and area equivalent radius r2 of each particle are calculated respectively. The sphericity is then r2 / r1, and the average value is taken to obtain the sphericity of the silicon-based material.

[0074] In this invention, the outer casing includes a steel casing, an aluminum casing, or a titanium casing. The negative electrode includes at least one first negative electrode and at least one second negative electrode; the first negative electrode is located on the outermost side of the electrode assembly, and includes a first negative current collector. The first negative current collector includes a first surface and a second surface disposed opposite each other along its thickness direction. The first surface is provided with a first negative active layer, the first surface being close to the center of the electrode assembly, and the second surface being away from the center of the electrode assembly. The second negative electrode includes a second negative current collector and a second negative active layer disposed on both sides of the second negative current collector. The thickness of the first negative current collector is h3.

[0075] In one example, the thickness h2 of the adhesive layer is less than the thickness h3 of the first negative electrode current collector. This avoids uneven thickness at the adhesive layer, which could lead to adhesion failure and wrinkles during formation, capacity testing, or long-term cycling. It also prevents excessive swelling of the adhesive layer due to excessive electrolyte absorption, which could cause bonding failure. Furthermore, it increases the bending strength of the first negative electrode sheet, thus suppressing electrode curling and preventing excessive binding between the adhesive layer and the first negative electrode sheet, which could lead to localized tearing of the first negative electrode current collector.

[0076] The batteries can all be assembled in accordance with conventional methods in the field.

[0077] It should be noted that the numerical designations such as "first" and "second" in this invention are only used to distinguish different substances or methods of use, and do not represent a difference in order.

[0078] The present invention will be described in detail below through embodiments. The embodiments described herein are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0079] In the following examples, unless otherwise specified, all materials used are commercially available analytical grade.

[0080] The following examples illustrate the lithium-ion secondary battery of the present invention.

[0081] Example 1-1 (1) Preparation of positive electrode sheet Lithium cobalt oxide, polyvinylidene fluoride (PVDF) binder, and conductive agent (carbon black and carbon nanotubes in a mass ratio of 2:1) are mixed in a mass ratio of 98:1:1. N-methylpyrrolidone solvent is added and the mixture is stirred under vacuum until a uniform and fluid positive electrode active layer slurry is formed. The slurry is then uniformly coated on both sides of an aluminum foil, and then baked, rolled, and die-cut to obtain the positive electrode sheet. (2) Preparation of negative electrode sheet Graphite, silicon carbide material, conductive agent (carbon black and carbon nanotubes in a mass ratio of 1:1), sodium carboxymethyl cellulose, and styrene-butadiene rubber were mixed in a ratio of 78:20:1:0.5:0.5. Deionized water was added, and the mixture was stirred under vacuum to prepare a negative electrode active layer slurry. This slurry was uniformly coated on both sides of a copper foil, and then baked, rolled, and die-cut to obtain the negative electrode sheet. The negative electrode active layer contained 12% silicon by mass, the average particle size D1 of the graphite was 15 μm, the average particle size D2 of the silicon carbide material was 8.5 μm, and the sphericity of the silicon carbide material was 0.8. (3) Preparation of electrolyte In an argon-filled glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), EC, PC, PP, and EP were mixed thoroughly as the base solvent. Then, fully dried LiPF6 was rapidly added and dissolved. FEC and 1,3,6-hexanetrionitrile were added sequentially, and the mixture was stirred until homogeneous. After passing moisture and free acid tests, the desired electrolyte was obtained. The mass ratio of EC to PC was 1:1, and the mass ratio of PP to EP was 5:2. Based on the total mass of the electrolyte, the mass content of LiPF6 was 16%, the mass content of 1,3,6-hexanetrionitrile was 3%, C1 was 35%, C2 was 20%, C3 was 26%, and (C2+C3) / C1 was 1.31. (4) Battery preparation The positive electrode sheet, separator (a 9 μm thick polyethylene film coated with a 2 μm thick alumina ceramic layer on one side of the polyethylene film, and then coated with a 0.5 μm thick polymethyl methacrylate adhesive layer on both sides) and negative electrode sheet prepared in step (2) are stacked in sequence to ensure that the separator is between the positive and negative electrode sheets to play a role in isolation. Then, the electrode assembly (stacked core structure) is stacked in sequence. On the third surface, fourth surface and second end face of the stacked core structure, the parts of the separator that extend out of the negative electrode sheet are bonded to each other to form a separator heat-sealing area. The separator heat-sealing area is then attached to the third surface, fourth surface and second end face of the stacked core structure. Then, the electrode assembly is stacked on the side surface according to Figure 1The adhesive paper (including a first adhesive paper, a second adhesive paper, and a third adhesive paper, the adhesive paper including a polyethylene substrate layer and an adhesive layer containing butyl acrylate-methyl acrylate-hydroxyethyl acrylate copolymer coated on the surface of the substrate layer, w1 is 55%) is set in the manner shown. The adhesive paper includes a first region and a second region. The second region of the adhesive paper covers at least part of the above-mentioned separator hot edge region. The electrode assembly with the above-mentioned adhesive paper is placed in a steel shell. The electrolyte prepared in step (3) is injected into the outer packaging. After vacuum sealing, standing, formation, shaping, sorting and other processes, a lithium-ion battery is obtained. The sum of the areas of the adhesive layers, S, is 0.2 dm. 2 The residual electrolyte coefficient K is 1.5, and K / S is 7.5; the coverage θ1 of the gel layer in the first region per unit area is 100% / 625μm. 2 The coverage θ2 of the adhesive layer in the second zone per unit area is 4.5% / 625μm. 2 The air permeability of the second region G2 is 80S / 100cc, and the ratio of G1 to G2 is 12.5; the thickness of the substrate layer h1 is 7μm, the thickness of the adhesive layer h2 is 6μm, the thickness of the first negative electrode current collector h3 is 15μm, the pore size of the substrate layer is 55nm, and the porosity of the substrate layer is 50%.

[0082] Examples 1-2 (1) Preparation of positive electrode sheet Lithium cobalt oxide, polyvinylidene fluoride (PVDF) binder, and conductive agent (carbon black and carbon nanotubes in a mass ratio of 2:1) are mixed in a mass ratio of 98:1:1. N-methylpyrrolidone solvent is added and the mixture is stirred under vacuum until a uniform and fluid positive electrode active layer slurry is formed. The slurry is then uniformly coated on both sides of an aluminum foil, and then baked, rolled, and die-cut to obtain the positive electrode sheet. (2) Preparation of negative electrode sheet Graphite, silicon carbide material, conductive agent (carbon black and carbon nanotubes in a mass ratio of 1:1), sodium carboxymethyl cellulose, and styrene-butadiene rubber were mixed in a ratio of 78:20:1:0.5:0.5, deionized water was added, and the mixture was stirred under vacuum to prepare a negative electrode active layer slurry. This slurry was uniformly coated on both sides of a copper foil, and then baked, rolled, and die-cut to obtain the negative electrode sheet. The negative electrode active layer contained 12% silicon by mass, the average particle size D1 of the graphite was 10 μm, the average particle size D2 of the silicon carbide material was 2 μm, and the sphericity of the silicon carbide material was 0.6. (3) Preparation of electrolyte In an argon-filled glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), EC, PC, PP, and EP were mixed thoroughly as the base solvent. Then, fully dried LiPF6 was rapidly added and dissolved. FEC and 1,3,6-hexanetrionitrile were added sequentially, and the mixture was stirred until homogeneous. After passing moisture and free acid tests, the desired electrolyte was obtained. The mass ratio of EC to PC was 1:1, and the mass ratio of PP to EP was 5:2. Based on the total mass of the electrolyte, the mass content of LiPF6 was 16%, the mass content of 1,3,6-hexanetrionitrile was 3%, C1 was 21%, C2 was 20%, C3 was 40%, and (C2+C3) / C1 was 2.86. (4) Battery preparation The positive electrode sheet, separator (a 9 μm thick polyethylene film coated with a 2 μm thick alumina ceramic layer on one side of the polyethylene film, and then coated with a 0.5 μm thick polymethyl methacrylate adhesive layer on both sides) and negative electrode sheet prepared in step (2) are stacked in sequence to ensure that the separator is between the positive and negative electrode sheets to play a role in isolation. Then, the electrode assembly (stacked core structure) is stacked in sequence. On the third surface, fourth surface and second end face of the stacked core structure, the parts of the separator that extend out of the negative electrode sheet are bonded to each other to form a separator heat-sealing area. The separator heat-sealing area is then attached to the third surface, fourth surface and second end face of the stacked core structure. Then, the electrode assembly is stacked on the side surface according to Figure 1 The adhesive paper (including a first adhesive paper, a second adhesive paper, and a third adhesive paper, the adhesive paper including a polyethylene substrate layer and an adhesive layer containing butyl acrylate-methyl acrylate-hydroxyethyl acrylate copolymer coated on the surface of the substrate layer, w1 is 40%) is set in the manner shown. The adhesive paper includes a first region and a second region. The second region of the adhesive paper covers at least part of the above-mentioned separator hot edge region. The electrode assembly with the above-mentioned adhesive paper is placed in a steel shell. The electrolyte prepared in step (3) is injected into the outer packaging. After vacuum sealing, standing, formation, shaping, sorting and other processes, a lithium-ion battery is obtained. The sum of the areas of the adhesive layers, S, is 0.38 dm. 2 The residual electrolyte coefficient K is 1.52, and K / S is 4; the coverage θ1 of the gel layer in the first region per unit area is 100% / 625μm. 2 The coverage θ2 of the adhesive layer in the second zone per unit area is 10% / 625μm. 2 The air permeability of the second region, G2, is 200S / 100cc, and the ratio of G1 to G2 is 5. The thickness of the substrate layer, h1, is 5μm, the thickness of the adhesive layer, h2, is 6μm, the thickness of the first negative electrode current collector, h3, is 15μm, the pore size of the substrate layer is 40nm, and the porosity of the substrate layer is 30%.

[0083] Examples 1-3 (1) Preparation of positive electrode sheet Lithium cobalt oxide, polyvinylidene fluoride (PVDF) binder, and conductive agent (carbon black and carbon nanotubes in a mass ratio of 2:1) are mixed in a mass ratio of 98:1:1. N-methylpyrrolidone solvent is added and the mixture is stirred under vacuum until a uniform and fluid positive electrode active layer slurry is formed. The slurry is then uniformly coated on both sides of an aluminum foil, and then baked, rolled, and die-cut to obtain the positive electrode sheet. (2) Preparation of negative electrode sheet Graphite, silicon carbide material, conductive agent (carbon black and carbon nanotubes in a mass ratio of 1:1), sodium carboxymethyl cellulose, and styrene-butadiene rubber were mixed in a ratio of 78:20:1:0.5:0.5, deionized water was added, and the mixture was stirred under vacuum to prepare a negative electrode active layer slurry. This slurry was uniformly coated on both sides of a copper foil, and then baked, rolled, and die-cut to obtain the negative electrode sheet. The negative electrode active layer contained 12% silicon by mass, the average particle size D1 of the graphite was 20 μm, the average particle size D2 of the silicon carbide material was 15 μm, and the sphericity of the silicon carbide material was 0.95. (3) Preparation of electrolyte In an argon-filled glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), EC, PC, PP, and EP were mixed thoroughly as the base solvent. Then, fully dried LiPF6 was rapidly added and dissolved. FEC and 1,3,6-hexanetrionitrile were added sequentially, and the mixture was stirred until homogeneous. After passing moisture and free acid tests, the desired electrolyte was obtained. The mass ratio of EC to PC was 1:1, and the mass ratio of PP to EP was 5:2. Based on the total mass of the electrolyte, the mass content of LiPF6 was 16%, the mass content of 1,3,6-hexanetrionitrile was 3%, C1 was 40%, C2 was 20%, C3 was 21%, and (C2+C3) / C1 was 1.03. (4) Battery preparation The positive electrode sheet, separator (a 9 μm thick polyethylene film coated with a 2 μm thick alumina ceramic layer on one side of the polyethylene film, and then coated with a 0.5 μm thick polymethyl methacrylate adhesive layer on both sides) and negative electrode sheet prepared in step (2) are stacked in sequence to ensure that the separator is between the positive and negative electrode sheets to play a role in isolation. Then, the electrode assembly (stacked core structure) is stacked in sequence. On the third surface, fourth surface and second end face of the stacked core structure, the parts of the separator that extend out of the negative electrode sheet are bonded to each other to form a separator heat-sealing area. The separator heat-sealing area is then attached to the third surface, fourth surface and second end face of the stacked core structure. Then, the electrode assembly is stacked on the side surface according to Figure 1The adhesive paper (including a first adhesive paper, a second adhesive paper, and a third adhesive paper, the adhesive paper including a polyethylene substrate layer and an adhesive layer containing butyl acrylate-methyl acrylate-hydroxyethyl acrylate copolymer coated on the surface of the substrate layer, w1 is 70%) is set in the manner shown. The adhesive paper includes a first region and a second region. The second region of the adhesive paper covers at least part of the above-mentioned separator hot edge region. The electrode assembly with the above-mentioned adhesive paper is placed in a steel shell. The electrolyte prepared in step (3) is injected into the outer packaging. After vacuum sealing, standing, formation, shaping, sorting and other processes, a lithium-ion battery is obtained. The sum of the areas of the adhesive layers, S, is 0.038 dm. 2 The residual electrolyte coefficient K is 1.52, and K / S is 40; the coverage θ1 of the gel layer in the first region per unit area is 100% / 625μm. 2 The coverage θ2 of the adhesive layer in the second zone per unit area is 0% / 625μm 2 The air permeability of the second region is G2, which is 50S / 100cc, and the ratio of G1 to G2 is 20. The thickness of the substrate layer is h1, which is 40μm; the thickness of the adhesive layer is h2, which is 6μm; the thickness of the first negative electrode current collector is h3, which is 15μm; the pore size of the substrate layer is 60nm; and the porosity of the substrate layer is 40%.

[0084] Example 2 group This set of embodiments follows the same principles as Embodiment 1-1, except that the sum of the areas S of the adhesive layers on the electrode assembly and the residual electrolyte coefficient K of the battery are changed to adjust K / S, in order to verify the effect of changing K / S, as follows: Example 2-1, S is 0.47 dm 2 K is 1.18 g / Ah, K / S is 2.51; θ2 is 49% / 625 μm 2 G2 is 500S / 100cc, G1 / G2 is 2; Example 2-2, S is 0.03 dm 2 K is 1.56 g / Ah, K / S is 60; θ2 is 0% / 625 μm 2 G2 is 50 seconds per 100 cc, while G1 / G2 is 20 seconds per 100 cc. Examples 2-3, S is 0.2 dm 2 K is 1.1 g / Ah, and K / S is 5.5; Examples 2-4, S is 0.2 dm 2 K is 2g / Ah, and K / S is 10.

[0085] Example 3 Group This set of examples follows the same procedures as Example 1-1, except that the mass content w1 of the first monomer in the adhesive polymer is changed to verify the effect of the change in w1, as follows: Example 3-1, w1 is 40%; Example 3-2, w1 is 70%.

[0086] Example 4 group This set of embodiments refers to Embodiment 1-1, except that the thickness h1 of the substrate layer, the thickness h2 of the adhesive layer, or the thickness h3 of the first negative electrode current collector are changed to verify the effect of the change of h1, h2, or h3, as follows: Example 4-1: h1 is 5 μm, h2 is 2 μm, and h3 is 15 μm; Example 4-2, h1 is 50 μm, h2 is 12 μm, and h3 is 15 μm; In Examples 4-3, h1 is 7 μm, h2 is 15 μm, and h3 is 10 μm.

[0087] Example 5 group This set of embodiments follows the same principles as Embodiment 1-1, except that the pore size and porosity of the substrate layer are changed to verify the effects of these changes, as detailed below: Example 5-1: The pore size of the substrate layer is 10 nm, and the porosity of the substrate layer is 20%. Example 5-2: The pore size of the substrate layer is 100 nm, and the porosity of the substrate layer is 80%.

[0088] Example 6 group This set of examples follows the same principles as Example 1-1, except that the mass content of carboxylic acid esters (C1), fluoroethylene carbonate (C2), and non-fluoro cyclic carbonates (C3) in the electrolyte are changed to adjust the (C2+C3) / C1 ratio. This is used to verify the effect of changing the (C2+C3) / C1 ratio, as detailed below: Example 6-1: C1 is 68%, C2 is 5.5%, C3 is 7.5%, and (C2+C3) / C1 is 0.19; Example 6-2: C1 is 62.3%, C2 is 5%, C3 is 13.7%, and (C2+C3) / C1 is 0.3; Example 6-3: C1 is 13.5%, C2 is 25%, C3 is 42.5%, and (C2+C3) / C1 is 5. In Examples 6-4, C1 was 7.4%, C2 was 25%, C3 was 48.6%, and (C2+C3) / C1 was 9.95. In Examples 6-5, C1 is 6%, C2 is 25%, C3 is 50%, and (C2+C3) / C1 is 12.5.

[0089] Example 7 This embodiment is based on Embodiment 1-1, except that the electrode assembly has a wound core structure. The positive electrode sheet, separator, and negative electrode sheet are stacked and wound to form a wound core. The electrode assembly has a third end face and a fourth end face arranged opposite each other along the height direction. The adhesive tape includes a fourth adhesive tape and a fifth adhesive tape, each independently including a first region and a second region. Specifically, the first region of the fourth adhesive tape covers a portion of the first surface and a portion of the second surface, and the second region of the fourth adhesive tape covers a portion of the third end face; the first region of the fifth adhesive tape covers a portion of the first surface and a portion of the second surface, and the second region of the fifth adhesive tape covers a portion of the fourth end face.

[0090] Comparative Example 1 This comparative study follows the same principles as Example 1-1, except that the sum of the areas S of the adhesive layers on the electrode assembly and the residual electrolyte coefficient K of the battery are changed to adjust K / S, in order to verify the effect of changing K / S, as follows: Comparative Example 1-1, S is 0.6 dm 2 K is 1.5 g / Ah, K / S is 2.5; θ2 is 100% / 625 μm 2 G2 is 1000S / 100cc, G1 / G2 is 1; Comparative Examples 1-2, S is 0.2 dm 2 K is 0.85 g / Ah, and K / S is 4.25; Comparative Examples 1-3, S = 0.2 dm 2 K is 2.3 g / Ah, and K / S is 11.5; Comparative Examples 1-4, S = 0.5 dm 2 K is 1.1 g / Ah, K / S is 2.2; θ2 is 49% / 625 μm 2 G2 is 500S / 100cc, G1 / G2 is 2; Comparative Examples 1-5, S = 0.03 dm 2 K is 1.7 g / Ah, K / S is 65.38; θ2 is 0% / 625 μm 2 G2 is 50S / 100cc, and G1 / G2 is 20.

[0091] Test case (1) Structural stability test of the battery After formation and capacity testing, the batteries were charged to full capacity (100% SOC) using a constant current and constant voltage at 0.5C. After being left to stand for 30 minutes in an environment of 25℃±2℃, a simulated drop test was performed: the batteries were dropped from a height of 1.0m onto a 18mm-20mm thick hard wooden board using the first surface, second surface, each side surface, and the corners, with one drop in each direction. After the test, a CT scan was performed on the batteries. Subsequently, the batteries were disassembled in a dry environment, the electrode assemblies were removed, and their condition was observed and recorded. The evaluation criteria for battery structural stability are based on the degree of misalignment of the outermost and innermost positive electrode edges on the same side, divided into four levels: Level 1 indicates a positive electrode edge misalignment of 0mm-0.5mm, denoted by "1"; Level 2 indicates a positive electrode edge misalignment of 0.5mm-1.5mm (excluding 0.5mm), denoted by "2"; Level 3 indicates a positive electrode edge misalignment of 1.5mm-3mm (excluding 1.5mm), denoted by "3"; and Level 4 indicates a positive electrode edge misalignment greater than 3mm, denoted by "4". The lower the score in levels 1-4, the better the structural stability of the battery under mechanical impact, and the higher the reliability of the adhesive tape binding the electrode assembly. The test results are recorded in Table 1.

[0092] (2) Lithium plating test of negative electrode In a 25℃ environment, the charging time for 10%-80% SOC was controlled at 11 minutes (SOC is the battery's state of charge; a fully charged battery is 100% SOC, and an empty battery is 0% SOC), the charging time for 0-10% SOC was 5 minutes, the charging time for 80-100% SOC was 20 minutes, and the discharging time was 60 minutes. This charge-discharge cycle test was performed on the battery using this charge-discharge regime. One charge and one discharge are called one cycle. After being fully charged, the battery was allowed to stand for 30 minutes before being discharged. This fast charging regime was used to perform charge-discharge cycle tests until 50 charge-discharge cycles were completed. On the 51st cycle, the battery was fully charged (100% SOC) using the fast charging regime. The battery was then removed and disassembled to observe the lithium plating state on the surface of the negative electrode. The evaluation criteria for lithium plating on the negative electrode are as follows: no lithium plating is Level 1, represented by "1"; slight lithium plating (lithium plating area on the negative electrode surface is less than 6%) is Level 2, represented by "2"; slight lithium plating (lithium plating area on the negative electrode surface is greater than or equal to 6% to 30%) is Level 3, represented by "3"; lithium plating (lithium plating area on the negative electrode surface is greater than 30% to 70%) is Level 4, represented by "4"; and severe lithium plating (lithium plating area on the negative electrode surface is greater than 70%) is Level 5, represented by "5". The test results are recorded in Table 1.

[0093] (3) Loop testing Under an environment of 25℃±2℃, the battery was discharged at 0.5C to a cutoff voltage of 3.0V and allowed to stand for 10 minutes; then charged at 2.5C constant current and constant voltage to 4.26V, with a cutoff current of 1.8C; charged at 1.8C constant current and constant voltage to 4.3V, with a cutoff current of 1C; charged at 1C constant current and constant voltage to 4.4V, with a cutoff current of 0.5C; and charged at 0.5C constant current and constant voltage to the upper limit voltage of 4.52V, with a cutoff current of 0.05C. This charge-discharge cycle was repeated 1000 times, and the discharge capacity at this point was recorded as the capacity after the cycle. The cycle capacity retention rate is calculated as: Cycle Capacity × 100% / Initial Capacity. The cycle capacity retention rate is recorded in Table 1.

[0094] (4) Electrolyte wettability test The lithium-ion battery was tested using an ultrasonic scanner. The battery was placed in the ultrasonic scanning cell for scanning. The emission voltage was 200V, the sampling frequency was 50 MHz, the pulse width was 1000ns, and the sampling voltage range was 2V. The criteria for judging electrolyte wettability were as follows: 1) If the entire electrode assembly area is yellow or green, it indicates good wettability, indicated by "0"; 2) If the electrode assembly area is blue and the blue area is less than 5% of the electrode assembly area, it indicates slight poor wettability, indicated by "1"; 3) If the blue area is between 5% and 10% of the electrode assembly area, it indicates poor wettability, indicated by "2"; 4) If the blue area is greater than 10% of the electrode assembly area, it indicates severe poor wettability, indicated by "3". The test results are recorded in Table 1.

[0095] Table 1 As can be seen from Table 1, the battery prepared by the present invention can effectively improve the wettability of the electrolyte to the electrode assembly and maintain the binding stability of the adhesive paper to the electrode assembly compared with the comparative example, thereby significantly improving the interfacial stability of the adhesive paper and the long-cycle stability of the battery.

[0096] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A battery, characterized in that, include: shell; An electrode assembly is located inside the housing, and the electrode assembly includes a positive electrode, a separator, and a negative electrode. Along a first direction of the electrode assembly, the diaphragm is spaced between the positive electrode and the negative electrode; the electrode assembly has a first surface and a second surface disposed opposite to each other along the first direction, and a side surface connecting the first surface and the second surface; The electrode assembly further includes adhesive tape extending from the first surface through the side surface to the second surface, and the adhesive tape is respectively bonded to at least a portion of the first surface and at least a portion of the second surface; the adhesive tape includes a first region and a second region, the first region being located on both sides of the second region, the first region covering at least a portion of the first surface and at least a portion of the second surface, and the second region covering at least a portion of the side surface; The adhesive tape includes a substrate layer and an adhesive layer located on at least one surface of the substrate layer; the sum of the areas of the adhesive layers on the adhesive tape of the electrode assembly is S, 0.01 dm. 2 ≤S≤0.5dm 2 The coverage of the adhesive layer in the first area per unit area is θ1, and the coverage of the adhesive layer in the second area per unit area is θ2, wherein θ1 > θ2. The residual liquid coefficient K of the battery satisfies: 1.1g / Ah≤K≤2g / Ah; K and S satisfy: 2.5≤K / S≤60.

2. The battery according to claim 1, wherein, 0.03dm 2 ≤S≤0.4dm 2 ; And / or, 4 ≤ K / S ≤ 40; And / or, 50% / 625μm 2 ≤θ1≤100% / 625μm 2 ; And / or, 0% / 625μm 2 ≤θ2≤49% / 625μm 2 ; And / or, the negative electrode sheet includes a negative current collector and a negative active layer located on at least one side of the surface of the negative current collector, the negative active layer includes a silicon-based material, and the mass content of silicon element in the negative active layer is 4%-60%; preferably 5%-50%.

3. The battery according to claim 1 or 2, wherein, The battery further includes an electrolyte, which comprises a carboxylic acid ester, and the carboxylic acid ester includes at least one of ethyl propionate, propyl propionate, and ethyl butyrate. Preferably, the mass content (C1) of the carboxylic acid ester in the electrolyte is 5%-68%; more preferably, it is 8%-40%.

4. The battery according to claim 3, wherein, The electrolyte also includes fluoroethylene carbonate; Preferably, the mass content (C2) of the fluoroethylene carbonate in the electrolyte is 5%-25%.

5. The battery according to claim 4, wherein, The electrolyte also includes non-fluorinated cyclic carbonates, which include ethylene carbonate and / or propylene carbonate. Preferably, the mass content (C3) of the non-fluorinated cyclic carbonate in the electrolyte is 5%-50%.

6. The battery according to claim 5, wherein, 0.3≤(C2+C3) / C1≤10; preferably, 0.3≤(C2+C3) / C1≤5.

7. The battery according to claim 1 or 2, wherein, The substrate layer includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinyl chloride, polytetrafluoroethylene, polyacrylonitrile, polyamide, polyimide, polyethylene terephthalate, polybutylene terephthalate, poly(p-phenylene terephthalate), poly(m-phenylene isophthalate), and their derivatives. And / or, the adhesive layer comprises a polymer, the polymer comprising at least one of the following groups: carboxyl, ester, hydroxyl, phenyl, cyano, epoxy, amino, phenolic hydroxyl, urethane, carbon-carbon double bond, carbonyl, methyl, methylene and carbon-hydrogen bond on an aromatic ring; Preferably, the monomers forming the polymer include at least one of a first monomer, a second monomer, and a third monomer; the first monomer includes at least one of n-butyl acrylate, ethyl acrylate, n-octyl acrylate, isobutyl acrylate, nonyl acrylate, n-decyl acrylate, lauryl methacrylate, lauryl acrylate, isodecyl acrylate, isoprene, butadiene, ethylene, and butene; the second monomer includes at least one of vinyl acetate, methyl acrylate, methyl methacrylate, styrene, acrylonitrile, ethyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate, and isobornyl acrylate; the third monomer includes at least one of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, 4-hydroxybutyl acrylate, ethylene glycol, acrylic acid, methacrylic acid, acrylamide, methacrylamide, N,N-dimethylacrylamide, and glycidyl methacrylate; More preferably, the monomers forming the polymer include at least two of the first monomer, the second monomer, and the third monomer, wherein the mass content w1 of the first monomer in the polymer is 40%-70%.

8. The battery according to claim 1 or 2, wherein, The thickness h1 of the substrate layer is 5μm-50μm; preferably 5μm-40μm. And / or, the thickness h2 of the adhesive layer is 2μm-12μm.

9. The battery according to claim 1 or 2, wherein, The air permeability of the first zone is G1, and the air permeability of the second zone is G2, where G1 / G2 > 1.5; Preferably, G2 is 50S / 100cc-500S / 100cc; And / or, the substrate layer includes a porous structure, wherein the pore size of the substrate layer is 10nm-100nm; And / or, the porosity of the substrate layer is 20%-80%, preferably 30%-50%.

10. The battery according to claim 1 or 2, wherein the negative electrode further comprises a carbon-based material, the carbon-based material comprising at least one of graphite, hard carbon, and soft carbon; And / or, the silicon-based material includes at least one of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy; And / or, the average particle size D1 of the carbon-based material is 10 μm-20 μm; And / or, the average particle size D2 of the silicon-based material is 2μm-15μm; And / or, the sphericity of the silicon-based material is 0.6-1.